2007
DOI: 10.1080/02841860701373595
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-18 gene promoter polymorphisms and the risk of esophageal squamous cell carcinoma

Abstract: This study shows for the first time an association between IL-18 gene promoter -137 G/C polymorphism may contribute represent a genetic risk factor for ESCC in a Chinese population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 25 publications
3
33
0
Order By: Relevance
“…Similarly, Khalili-Azad et al found no such association with breast cancer in a population of the same ethnic background [17], despite a positive association with IL-18 promoter polymorphism. In contrast, Wei et al [11] and Liu et al [12] found an association between IL-18 promoter haplotype and esophageal squamous cell carcinoma and prostate cancer in Chinese populations. These conflicting data may be due to differences in the linkage disequilibrium in different ethnic backgrounds.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Similarly, Khalili-Azad et al found no such association with breast cancer in a population of the same ethnic background [17], despite a positive association with IL-18 promoter polymorphism. In contrast, Wei et al [11] and Liu et al [12] found an association between IL-18 promoter haplotype and esophageal squamous cell carcinoma and prostate cancer in Chinese populations. These conflicting data may be due to differences in the linkage disequilibrium in different ethnic backgrounds.…”
Section: Discussionmentioning
confidence: 91%
“…Although the functional consequence of -656 polymorphism is not clear, -607 and -137 SNPs can cause differences in transcription factor binding, and may have an impact on IL-18 expression [10]. IL-18 promoter polymorphisms (-607 or -137) were previously shown to be statistically associated with esophageal squamous cell carcinoma [11] and prostate cancer [12] in Chinese populations, colorectal cancer in a Greek population [13], ovarian cancer in native Hawaiians [14], and breast cancer in Iranians [17]. In contrast, there was no significant association between IL-18 polymorphism and squamous cell carcinoma of the head and neck in Iran [16], or with squamous oral carcinoma in Greece [15].…”
Section: Discussionmentioning
confidence: 99%
“…Haplotype analysis showed statistical significance in patients with stomach cancer -607 C/-137 C and -607 A/-137 G and in patients with colorectal cancer and esophageal squamous cell carcinoma (Wei et al, 2007;Haghshenas et al, 2009). …”
Section: Il-18 Gene Promoter Polymorphismmentioning
confidence: 95%
“…Variations in the IL-18 gene promoter are able to influence IL-18 production and activity. While results are still inconclusive, several emerging studies have reported the associations between -607 C/A polymorphism in the IL-18 gene and gastrointestinal cancer risk (Nikiteas et al, 2007;Wei et al, 2007;Haghshenas et al, 2009;Babar et al, 2012). This controversy may due to several factors, including differences between cancer sites, ethnicity, sample sizes, study designs and assay characteristics.…”
Section: Discussionmentioning
confidence: 83%
“…Based on our preliminary search criteria, 712 were excluded as they did not satisfy the inclusion criteria. Finally, five case-control studies from four publications with 1618 cases and 1155 controls were included in the meta-analysis (Nikiteas et al, 2007;Wei et al, 2007;Haghshenas et al, 2009;Babar et al, 2012). All the included journal articles were published between 2007 and 2012.Three of these studies were conducted in Asian populations, and two in Caucasian populations.…”
Section: Study Characteristicsmentioning
confidence: 99%